Boys, Bass and Bother Popular Dance and Identity in UK Drum 'n' Bass Club Culture - Hall, Jo (Palgrave Macmillan UK, 2018)
This book uses ethnographic research to examine the role of dance in the construction of identity in the distinctly British electronic dance music club culture of drum 'n' bass. Dancing is revealed as the central way in which drum 'n' bass clubbers construct and perform their identities, which are informed, although not defined, by the club culture's histories. The intertextual and intercultural development of drum 'n' bass musical and clubbing culture is shown to be represented in the dancing body, prompting a challenge to the discourse of cultural appropriation. Popular representations of identities are embodied by drum 'n' bass clubbers through affective transmission via the popular screen, and in this process are re-valued in their embodiment. Using a socially orientated understanding of intertextuality, the popular dancing body is shown to be heterocorporeal: containing traces of prior meaning and logic yet replete with new meaning and significance. .